Farm Women's Attitudes Toward Change in Work and Family Roles - Harriett K. Light; Ruth E. Martin; Doris Hertsgaard (Journal of Research in Rural Education, 1983)
Societyis experiencingrapid change in work and family roles. In order for schoolsto prepare students for these changes, knowledge of the families' attitudes toward such changes is necessary because the parents' influence on children is significant. Rural families have traditionally held more conservative views than urban families. However, there is some indication that the traditional conservatism of rural areas is giving way to increasingly liberal attitudes. This paper presents the findings of a study to assess the attitudes of 715 respondents from 2000 randomly selected farm women toward change in work and family roles. Significant differences in attitudes of women were found according to their age, number of children, and religious preference. Generally, attitudes regarding family roles were more conservative than were attitudes regarding career roles